Drug‐Related‐Problem Outcomes and Program Satisfaction from a Comprehensive Brown Bag Medication Review. Issue 9 (27th August 2015) - O'Connell, Mary Beth; Chang, Feng; Tocco, Ashley; Mills, Megan E.; Hwang, Jamie M.; Garwood, Candice L.; Khreizat, Hanan S.; Gupta, Nishi S.
<x xml:space="preserve">Abstract</x> Objectives To classify and quantify drug‐related problems (DRPs), determine acceptance of DRP recommendations, and assess medication review satisfaction. Design Comprehensive brown bag medication reviews. Setting Six senior centers and three senior high‐rises. Participants Individuals aged 60 and older (mean age 75.9 ± 8.5) taking five or more medications (n = 85). Measurements Two investigators independently classified DRPs using modified Pharmaceutical Care Network Europe classification scheme and severity of medication error and value of service scales. Two other investigators adjudicated classification differences. Satisfaction surveys were administered immediately and 3 months after review. A DRP recommendation implementation survey was completed at least 3 months after the review. Results Participants had a mean of 4.3 ± 2.8 DRPs (range 0–10). DRPs were classified as adverse reactions (30%), treatment effectiveness (28%), treatment costs (13%), information need (8%), and other (21%). Causes included drug selection (40%), wrong dosage (23%), participant problems (e.g., adherence, lack of medication knowledge, 16%), drug use process problems (12%), drug formulation (0.5%), treatment duration (0.5%), and other (7%). Interventions required drug changes (44%), prescriber input (37%), individual counseling (18%), or other (1%). DRP severities were significant (59%) or minor (35%). Participants expressed satisfaction with the program because they were able to ask questions, trusted the answers, and knew more about their medications. After 3 months, they had implemented 63% of the DRP recommendations. Conclusion Older adults found the medication review helpful and implemented 63% of the DRP recommendations.